(1/2)(-4+4) = 1 => (1/4)^(3/2x-4) = 1 ( bằng 1 khi mũ bằng 0 , vì a0=1 )
vậy ta có : (3/2x - 4 ) = 0 => x= 8/3
tích nha
Đúng 0
Bình luận (0)
(1/2)(-4+4) = 1 => (1/4)^(3/2x-4) = 1 ( bằng 1 khi mũ bằng 0 , vì a0=1 )
vậy ta có : (3/2x - 4 ) = 0 => x= 8/3
tích nha
|(x+1/2).|2x-3/4||=2x-3/4 tim x biet
Tim x,y,z biet:2(x-1)-3(2x+2)-4(2x+3)=16
tim x , biet :
1 ) 2017 - \ x - 2017 \ = x
2) -1/2 . ( 3x - 1 ) + 3/4 . ( 3-2x) = -3 . ( x/2 - 1 ) - ( 4/5) mu -1
tim x biet (2x-3)^2-4(x+1)^2=5
tim x biet (2x-3)^2-4.(x+1)^2=5
Tim x,y,z biet:2(x-1)-3(2x+2)-4(2x+3)=16
giai day du
tim x biet :
a) ( 2x^2+4 ) - (x^2-3/2 ) = (-3+4x^2)+ ( -4x^2/3+1)
b) ( I xI -4) - ( 2- I-xI ) = 1/3 . I xI -5
Tim xthuoc Z biet:
1,|2x-5|-|2x+9|=0
2,|x+1|-|x+2|-|3-x|=7
3,|2x+3|+|3x+2|-|4-x|=10
Tim x+y+z = ? biet (x-1) /2= (y-2) /3 = (z-3) /4 va 2x+3y-z=95